ANALISIS KONFLIK BATIN DAN PERWATAKAN AMBO ULENG DALAM NOVEL RINDU KARYA TERE LIYE ( KAJIAN PSIKOLOGI SASTRA) - Dayang Suhana; Susilawati, Ahmad Rathomi (ADISAM PUBLISHER, 2025)
This study aims to determine the factors of inner conflict and also character and the implications of learning Indonesian related to inner conflict and also character in the novel Rindu by Tere Liye. This study uses a qualitative approach with a type of library study research. The data collection technique used is the document, then the data analysis technique used in this study is the content analysis technique (content analysis) the subject for general content analysis is